Performance and Micro-Pacing Strategies in a Classic Cross-Country Skiing Sprint Race - Ihalainen, Simo; Colyer, Steffi; Andersson, Erik; McGawley, Kerry (Frontiers in Sports and Active Living, 2020)
The purpose of the present study was to analyze micro-pacing strategies in cross-country skiing, and their relation to section and total race times. Eleven competitive female cross-country skiers were tracked during a classic sprint time-trial race using a global navigation satellite system (GNSS) unit. A coordinate mapping procedure was applied to the GNSS unit measurements to analyze the instantaneous velocities and split times. The track was divided into nine sections and individual section times were calculated. Statistical parametric mapping (SPM) was used to analyze the relationships between instantaneous velocity and section or total race time. SPM analyses revealed two uphill sections and one flat section where greater instantaneous velocities were related to faster total race times. The first major uphill section on the track demonstrated a more conservative micro-pacing strategy (SPM supra-threshold clusters along the entire uphill, p<0.05-0.001) compared to the more aggressive strategy used in the last uphill section (clusters on the first half of the uphill, p<0.05-0.001). Faster flat section times were associated with greater instantaneous velocities throughout the section (p<0.001), while faster downhill section times were related to greater instantaneous velocities at the top of the downhill (p<0.001) and in the downhill turns (p<0.001). In conclusion, micro-pacing strategies were related to overall skiing performance and distinct track sections were identified where instantaneous velocities were related to section or total race times. In order to improve skiing performance, athletes could focus on more aggressive pacing early on in the “end spurt”, during the transitions from uphill to flat sections, and during the transitions from flat or uphill to downhill sections.